Paradoxes of democracy: Rousseau and Hegel on democratic deliberation. (January 2022) - Rustighi, Lorenzo
In this article, I engage with what relevant literature addresses as the 'paradox of democracy' and trace it back to the dialectic between authorization and representation established by social contract theories. To make my argument, I take Rousseau's Social Contract as a paradigmatic example of the paradox and analyse it in light of Hegel's critical response. My aim is to show that, although Rousseau rejects the idea of representing the popular will, representation resurfaces in his Republic from top to bottom and engenders a structural opposition between citizens and rulers: drawing on the Hegelian scrutiny of contractarianism, I focus on three key moments in Rousseau's theory, namely the Lawgiver, the majority rule and the executive power. After illustrating how the social contract undermines democratic participation in deliberative processes, I suggest that Hegel's philosophy of right overcomes the paradox by positively assuming it as a dialectical contradiction that requires a specific constitutional approach to democracy. In this sense, I argue, the Hegelian perspective on democratic deliberation helps us to better frame Rousseau's ambition to conceive the Republic as a free community of equals and urges us to elaborate a more coherent understanding of participation in a pluralistic society.